História e memória da Reforma Universitária da Pontifícia Universidade Católica de São Paulo (1979-1988) - Canha, Humberto Carlos Mairena (2013)
The goal of this research is to contribute to the History of University Reformation in Brazil, by analizing the participation of different university sectors in the process of reformation, democratization and autonomy of the Pontifícia Universidade Católica de São Paulo (PUC-SP) during the 1982 Constituinte, the democratic experiment and the institutional crisis, between years 1979 and 1988. It aims to understand how these meaningful moments in the University's memory, directly opposite of the military government and its limiting and repressive educational policies, revealed themselves and came together in the institution. Its starting point is the hypothesis that the reconciliating discourse disguised differing political stands, which were not strong enough to make opposition to the predominant one and thus substantially alter the understanding of the memory itself and the university's history and the current moment. The institutional crisis revealed conflicts between different sectors, questioning about the "PUCkian Democracy" and different alternatives about the future of the university among the supporters of the "Statetization" and of the "Mixed Foundation", from 1986 on. Despite the democratic experiment and the institutional crisis, PUC-SP did not manage to equate its subordinate status to Fundação São Paulo, which was responsible for establishing the limits of the university's democracy and autonomy. Regarding historiographic material production and the institution's memory this research analyzed the discourse broadcast in documents produced by different sectors, mainly those published by associations, community newspapers and the records of the University Counsil, recreating the sequence of actions, reasoning and meanings given to the historically built representations